IMF Staff papers, Volume 45 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1998)
This paper analyzes contagion and volatility with imperfect credit markets. The paper interprets contagion effects as an increase in the volatility of shocks impinging on the economy. The implications of this approach are analyzed in a model in which domestic banks borrow at a premium on world capital markets, and domestic producers borrow at a premium from domestic banks. Financial spreads depend on a markup that compensates lenders, in particular, for the expected cost of contract enforcement. Higher volatility increases financial spreads and the producers' cost of capital.